Identification of a 3-β-homoalanine conjugate of brusatol with reduced toxicity in mice. Issue 23 (1st December 2020) - Hwang, Nicky; Pei, Yonggang; Clement, Jason; Robertson, Erle S.; Du, Yanming
Graphical abstract: Abstract: Brusatol, a quassinoid natural product, is effective against multiple diseases including hematologic malignancies, as we reported recently by targeting the PI3Kγ isoform, but toxicity limits its further development. Herein, we report the synthesis of a series of conjugates of brusatol with amino acids and short peptides at its enolic hydroxyl at C-3. A number of conjugates with smaller amino acids and peptides demonstrated activities comparable to brusatol. Through in vitro and in vivo evaluations, we identified UPB-26, a conjugate of brusatol with a L- β-homoalanine, which exhibits good chemical stability at physiological pH's (SGF and SIF), moderate rate of conversion to brusatol in both human and rat plasmas, improved mouse liver microsomal stability, and most encouragingly, enhanced safety compared to brusatol in mice upon IP administration.